A study of gender roles in a globalized culture in selected works of Lualhati Bautista - Dominado, May Wan Posa. (2002.)
This descriptive study focuses on the portrayal of gender roles in globalized culture in selected works of Lualhati Bautista. The researcher tabulated the descriptions and redefinition of gender roles. Gender stereotypes and norms were also noted, including reasons for changes in gender roles. The results showed that although traditional gender roles still exist, individuals liberated themselves from repressive norms. Emerging discourse on gender transform the hierarchical nature of filipino society due to patriarchal discourse and practices. In a globalized culture, individuals are not limited by traditional normas of their gender role. They also seek other roles, which leads to legal equality. However, Filipino conciousness is still subjugated by colonial narratives. Globalization of culture does not liberate individuals, it continues the subjugation of Filipino culture.
Research Project (Undergraduate, Bachelor of Arts in Political Science-Psychology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Bautista, Lualhati -- Selected Works; Gender Roles